Ka-Band Lightweight High-Efficiency Wideband 3D Printed Reflector Antenna - Yu Zhai; Ding Xu; Yan Zhang (International Journal of Antennas and Propagation)
This paper presents a lightweight, cost-efficient, wideband, and high-gain 3D printed parabolic reflector antenna in the Ka-band. A 10 λ reflector is printed with polylactic acid- (PLA-) based material that is a biodegradable type of plastic, preferred in 3D printing. The reflecting surface is made up of multiple stacked layers of copper tape, thick enough to function as a reflecting surface (which is found 4 mm). A conical horn is used for the incident field. A center-fed method has been used to converge the energy in the broadside direction. The proposed antenna results measured a gain of 27.8 dBi, a side lobe level (SLL) of −22 dB, and a maximum of 61.2% aperture efficiency (at 30 GHz). A near-field analysis in terms of amplitude and phase has also been presented which authenticates the accurate spherical to planar wavefront transformation in the scattered field.